Management of tillering in the production of flower stems of heliconia cultivated in pots - Coelho, Jobson Paixão de Amorim; Gervásio, Eliezer Santurbano; Sá, Teógene Souza de; Cavalcante, Márkilla Zunete Beckmann; Souza, Sabrina Gomes de (Comunicata Scientiae, 2019)
Potted cultivation of tropical flowers presents good projections for the northeastern region of Brazil; however, it still faces some peculiarities regarding conduction and management. The objective of this study was to evaluate the effect of tillering on the production of Heliconia psittacorum L.f. cv. Red Opal, grown in flowerpot. The experiment was carried out in a protected environment at the Campus of Agricultural Sciences (CCA) of UNIVASF, Petrolina - PE, Brazil, between 2014 and 2016. A completely randomized design was used, with four tiller densities per pot (4, 8, 12 and 16 tillers) and eight replications, totaling 32 plots. The irrigation system was automated and monitored by weighing lysimetry. Were evaluated: efficiency of water use (EUA); harvested flower stems (HC); ratio of harvested stems and number of tillers (HC / NP); number of leaves (NF); duration of vegetative (DFV) and productive phases (DFP); total cycle (CT); floral stem length (CHF); floral stem diameter (DH), bracts length (CB) and equivalent diameter of the collar (DECH). The results were subjected to regression test. The EUA was higher in the density of 16 tillers pot-1; the HC variable presented an increasing linear trend; a decreasing linear trend was detected for HC/NP, NF, DFP, DH, CB and DECH. The number of tillers in the pot does not limit the emission of floral stems. However, the quality of these is inversely proportional to the tiller density.